The Role and Significance of Taṣawwuf in Modern-Day Crisis - Niyaz Ahmad Lone (Teosofia: Indonesian Journal of Islamic Mysticism, 2022)
The present manuscript aims to assess the important features of Taṣawwuf and its position in the contemporary world. Moreover, this study will help to understand the paramount role of Taṣawwuf in pulling out humanity from these crises and its importance in espousing the society in terms of socio-religious and spiritual development. The suggested methodology for this manuscript will be exploratory, descriptive, and historical to explore the contemporary importance of Taṣawwuf and its main characteristics. This study reveals the continuing significance of Taṣawwuf in modern times, where, religious extremism, violence, human value crises, social disharmony, and an imbalance between spirituality and mundane concerns of humanity are some issues that are confronting human beings in the contemporary world. Hence this study found that the legitimacy of Taṣawwuf in modern society still exists.Contribution: This article makes a new discovery regarding the continued existence of Taṣawwuf and its role in maintaining peace, harmony, and religious tolerance in contemporary society and also reveals the role of Taṣawwuf in the spiritual development of human beings and maintaining a balance between the spirituality and mundane ends.